To Identify Predictors of Central Lymph Node Metastasis in Patients with Clinically Node-Negative Conventional Papillary Thyroid Carcinoma - Jiru Yuan; Gang Zhao; Jialin Du; Xiaoyi Chen; Xiaodong Lin; Zhengbo Chen; Zeyu Wu (International Journal of Endocrinology)
Objective. The aim of this study was to identify the risk factors associated with central lymph node metastasis (CLNM) in patients with clinically node-negative conventional papillary thyroid carcinoma (cN0 CPTC). Methods. A total of 190 cN0 CPTC patients who underwent thyroidectomy with prophylactic central neck dissection (pCND) in the Department of General Surgery at Guangdong General Hospital between March 2014 and December 2015 were assessed retrospectively. The relations of CLNM with clinicopathologic characteristics of cN0 CPTC were analyzed by univariate and multivariate logistic regression. Results. The incidence of CLNM in patients with cN0 CPTC was 63.2% (120 of 190 cases). Univariate analysis showed that age <45 years (P=0.000), tumor size >2 cm (P=0.009), multifocality (P=0.001), and bilaterality (P=0.000) were significantly associated with the increased incidence of CLNM in cN0 CPTC. No significant correlations were found between CLNM and other variables such as gender (P=0.150), capsular invasion (P=0.973), extrathyroidal invasion (P=0.616), and lymphadenectomy (P=0.062). Multivariate logistic regression analysis revealed that age <45 years (P=0.000), tumor size >2 cm (P=0.025), and bilaterality (P=0.000) were independent risk factors of CLNM in patients with cN0 CPTC. Conclusions. Metastatic disease to central compartment lymph nodes is prevalent in patients with cN0 CPTC. Age <45 years, tumor size >2 cm, and bilaterality are independent risk factors of CLNM, which allow for selective CND in patients with cN0 CPTC.